Two separate neural pathways, lateral and medial, for sensory decisions in mammals: switching of attention between the outer and inner cognitive worlds - Mori, Kensaku; Sakano, Hitoshi (Frontiers in Neuroscience, 2025)
Mammalian sensory cortices detect changes both inside and outside of the body. They identify sensory information from the surrounding world, evaluate the current situation, and generate top-down signals to induce emotional and behavioral outputs. The cortices also detect physiological changes inside of the body, such as internal pain, thirst, fever, and retronasal odors. Thus, the cortical attention is directed to either the outside or inside of the body. As consciousness seems to be generated by sensory stimuli together with the recollected memory scene, self-cognition may be divided into two categories: one for the outside world and the other for the inside world. We have previously proposed that in the mammalian olfactory system, orthonasal and retronasal odor signals are separately detected in the inhalation and exhalation phases during respiration by the lateral and medial parts of the olfactory bulb, respectively. We further speculated that orthonasal and retronasal olfactory information are transmitted to the higher-order cognitive areas by the lateral pathway for outer-world information and medial pathway for inner-world information, respectively. In the present article, we propose that the late exhalation phase provides the time frame for generating internal attention and internal signals for behavioral and emotional outputs. We will discuss how the recognition of external objects is combined with internal emotion to generate associative memory of object-feeling, namely emotional episodic memory. It will also be discussed how the two types of attention directed toward the outer and inner worlds are switched from one to the other to reset self-cognition and consciousness.